GE_GERICHTE A/3383/2022 vom 25. Mai 2023 - GE Cour de justice (2023)
REMISE EN L'ÉTAT;ZONE AGRICOLE;PERMIS DE CONSTRUIRE;POUVOIR D'EXAMEN | Cst.9; Cst.5.al3; LCI.129.lete; LAT.22; LCI.1.al1; LaLAT.24c